Effects of Transient Electrical Acupuncture Stimulation Combined With Rehabilitation Training on Hemorheology, Neurological Function and BDNF in Patients With Cerebral Infarction - Chen, Shuangqin; Huang, Jianghua; Tang, Xuan; Wang, Ting; Zeng, Yahua (Frontiers in Surgery, 2022)
Objective To explore the effects of transient electric acupuncture stimulation combined with rehabilitation training on hemorheology, neurological function and brain-derived neurotrophic factor (BDNF) in patients with cerebral infarction (CI). Methods A total of 90 patients with CI were admitted to our hospital from March 2019 to March 2021. According to the random number table method, 90 patients were divided into a control group (was treated with transient electrical acupuncture stimulation intervention treatment) and a therapy group (was treated with rehabilitation training on the basis of the control group), with 45 cases in each group. NIHSS score to detect neurological deficit; FMA score to detect motor function recovery; the clinical efficacy of the two groups of patients were compared; blood rheology analyzer to detect whole blood high shear viscosity, whole blood low shear viscosity, platelet aggregation rate and fibrinogen indicators; ELISA detects the content of BDNF in serum. Results There was no significant difference in NIHSS score, FMA score, clinical efficacy, hemorheology index, and BDNF content between the two groups of patients before treatment (P > 0.05). After treatment, the NIHSS score, whole blood high shear visible, whole blood low shear visible, platelet aggregation rate and fibrinogen index of the two groups were lower than those before treatment, and the FMA score and BDNF content of the two groups were higher than those before treatment, and all the above indicators in the therapy group changed significantly compared with the control group (P < 0.05). After treatment, the clinical efficacy of the therapy group was better than that of the control group (P < 0.05). Conclusion The combination of transient electrical acupuncture stimulation and rehabilitation training can inhibit the blood flow index of patients with CI, improve the nerve function, increase the content of BDNF in the patient's serum, and restore the patient's nerve function.